Sustainable Hydrogen Production from Oil Palm Trunk Biomass in Indonesia: A Techno-Economic Study - Pancasakti, Bima Prasetya; Budhijanto (Universitas Muhammadiyah Yogyakarta, 2024)
Hydrogen has been recognized as a global sustainable alternative sustainable energy source. The government of Indonesia has been working on a novel idea to launch the hydrogen industry. Accordingly, research and development of ecologically acceptable hydrogen manufacturing methods are essential. Supercritical water gasification (SCWG) is one of the recent techniques to create hydrogen. This research investigated the techno-economics of hydrogen production in Indonesia using SCWG. Oil palm trunks (OPT), a plentiful byproduct of palm oil plants, are the primary raw materials employed in this industry. This study extracted data from several research publications on SCWG-related hydrogen generation and performed computational analysis using several economic parameter equations. According to the analysis, with a potential OPT source of around 34 million tons, the plant could manufacture 304,166.67 tons of OPT per year, generating 365,000 tons of hydrogen annually. The production cost was projected to be USD 1,179,409,295, with a fixed capital investment of USD 1,178,853,030.47. The expected annual income was USD 1,825,000,000. This assessment yielded an ROI of 60% and an NPV of USD 1,888,889,382.70. The IRR value was 26.96%, with a PoT of 2.49 years. The sensitivity analysis revealed that the price of hydrogen significantly affected the values of IRR and PoT. Therefore, the government must determine the exact price of hydrogen to ensure its sustainability.